2022
DOI: 10.1021/acsbiomedchemau.2c00063
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Protein Degradation for Infectious Diseases: from Basic Biology to Drug Discovery

Abstract: Targeted protein degradation (TPD) is emerging as one of the most innovative strategies to tackle infectious diseases. Particularly, proteolysis-targeting chimera (PROTAC)-mediated protein degradation may offer several benefits over classical anti-infective small-molecule drugs. Because of their peculiar and catalytic mechanism of action, antiinfective PROTACs might be advantageous in terms of efficacy, toxicity, and selectivity. Importantly, PROTACs may also overcome the emergence of antimicrobial resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…, neurodegenerative diseases and infective diseases. Overcoming the blood–brain barrier and co-opting other organismal ubiquitin-proteasome systems , are major hurdles for developing PROTACs against neurodegenerative disease targets and anti-infective diseases targets, respectively.…”
Section: Targeted Protein Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…, neurodegenerative diseases and infective diseases. Overcoming the blood–brain barrier and co-opting other organismal ubiquitin-proteasome systems , are major hurdles for developing PROTACs against neurodegenerative disease targets and anti-infective diseases targets, respectively.…”
Section: Targeted Protein Degradationmentioning
confidence: 99%
“…, neurodegenerative diseases and infective diseases. Overcoming the blood–brain barrier and co-opting other organismal ubiquitin-proteasome systems , are major hurdles for developing PROTACs against neurodegenerative disease targets and anti-infective diseases targets, respectively. How to fast expand the E3 ligase landscape and the E3 ligand toolbox. Cereblon is so far the most prevalent E3 ligase for the first wave of PROTACs in clinical trials.…”
Section: Targeted Protein Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…These distinctive features position PROTAC as a potential game-changing technology in drug discovery that has been widely explored for degrading various disease-causing proteins. Harnessing these advantages, antiviral PROTACs via targeted protein degradation has been considered as a promising strategy for developing next-generation antiviral drugs to combat infectious diseases. The antiviral PROTACs would improve resistance profiles to those of traditional inhibitors. , In our ongoing pursuit of COVID-19 drug discovery targeting M Pro , we present the design, synthesis, and evaluation of the first series of small-molecule PROTAC degraders targeting SARS-CoV-2 M Pro . Our work has led to the identification of MPD2 as a potent degrader of M Pro with a DC 50 value of 296 nM, demonstrating promising antiviral activity against various SARS-CoV-2 strains and exhibiting enhanced potency against nirmatrelvir-resistant viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolysis targeting chimera (PROTAC) technology provides an attractive approach to modulate protein levels of therapeutic target by hijacking the cellular machinery responsible for the physiological elimination of endogenous proteins. This strategy has been widely established to be successful in targeting cancer-related proteins, with more than a dozen drug candidates entering clinical investigation. On the contrary, the applicability of PROTAC technology in the field of antivirals remains marginal. Only a few studies of PROTAC molecules targeting viral proteins have been reported in the case of hepatitis and influenza viruses, and just a preliminary attempt investigating the applicability of PROTAC technology against coronaviruses (CoV) has been documented . The latter study targets the viral spike protein receptor binding domain of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
mentioning
confidence: 99%